Curriculum Change vs Changes in The Field: How Contextual is Learning in The Merdeka Curiculum? - St E Sururiyatul Mu’aziyah; Isnawati Isnawati (CV. Dharma Samakta Edukhatulistiwa, 2023)
The curriculum continues to change but the way teachers teach in teaching science, especially contextual learning does not change. This study aims to see how far the new curriculum (merdeka curriculum) can support teachers in providing contextual learning and what kind of support teachers need to implement an independent curriculum. The research method used is a case study on the learning process in driving schools and K-13 schools. The results of the observations show that there is no difference between the way teachers teach in the driving schools and the curriculum schools. Thus, other support is needed to support teachers in teaching contextual learning such as special training on contextual learning, teacher competency training, and special training to increase teacher motivation.